Fractographic approach to metallurgical coke failure analysis. Part 1: Cokes of single coal origin. (15th September 2016) - Roest, Richard; Lomas, Hannah; Hockings, Kim; Mahoney, Merrick R.
Highlights: Failure profiles for an individual metallurgical coke were constructed. Microstructural features in coke fracture surfaces were identified. Macro and micro failure mechanisms in the coke were quantified. Abstract: Metallurgical coke is a complex brittle heterogeneous material consisting of carbon derived from fusible, semi-fusible and inert coal particles that forms a porous composite matrix. This paper presents a novel approach to assess and quantify the breakage behaviour and microstructural weaknesses in a pilot oven metallurgical coke. The approach uses fractography, a method commonly applied to determine the fracture behaviour and origin(s) in homogeneous materials, such as metals and ceramics. Determination of the fracture origin(s), paths of crack propagation and microstructural weaknesses in such a complex heterogeneous material as metallurgical coke represents a significant advance in both the application of fractography and the assessment of coke strength and breakage behaviour. Identification of the key features that contribute to the coke's failure will facilitate better prediction of coke strength from coal properties and ultimately optimisation of the coal blending process. Key features and markings have been clearly identified on fracture surfaces that can either be traced back to the fracture origin or give an indication of the type of fracture or stresses to which the coke has been subjected, including the directionality and strength of those stresses. These markings include hackle, hackle twist and wallner lines, as well as markings generated by conchoidal and overload fractures. A three-step approach was applied to determine the breakage behaviour in stabilized lumps of the pilot oven coke, in which fractured coke surfaces were analysed at the macro, micro and submicron levels. The observed mechanisms of failure were quantified and summarised using a radar diagram.